The Relationship Between Anaerobic Endurance and the Performance of 400 Meter Runners in Ambon City - Biloro, Marson Arens; Rumahlewang, Emma; Tahapary, John Melvin (Peneliti.net, 2025)
This study aims to analyze the relationship between anaerobic endurance and the performance of 400-meter sprinters in Ambon City. The research background highlights the crucial role of anaerobic capacity in sustaining high-speed performance throughout the track, where the lactic energy system predominates. A quantitative correlational design was employed, involving 32 male and female athletes aged 18–25 years who participated in the 400-meter event. Anaerobic endurance was assessed using a 300-meter sprint test, while running performance was measured by the best completion time from two trials. Data were analyzed using the Pearson correlation test. Results revealed a moderate positive correlation between anaerobic endurance and 400-meter running performance (r = 0.50; tcount = 0.4205 > ttable = 0.3494, df = 30), indicating that higher anaerobic capacity corresponds to better athletic performance. These findings emphasize the importance of anaerobic training methods, such as high-intensity interval training (HIIT), to enhance sprint endurance and speed. This study contributes empirical evidence to the development of athletic training programs at the regional level